Canadian Prison Environments: A Mixed Methods Analysis - Weinrath, Michael (The prison journal, 2023)
The current study uses a mixed methods approach to assess quality of prison life in Canada's Atlantic provincial correctional institutions. Questions from the Measurement of the Quality of Prison Life were adapted to create scales to assess prisoner climate dimension perceptions, with open-ended questions providing qualitative data. Across eight prison sites, statistical analysis revealed between prison differences and confirmed that prison sentence location did matter. The qualitative data emergent themes also produced several consistent concerns that Likert responses could not capture, ranging from primary needs to service desires. Research affirms the importance of studying prison environments and supports the use of mixed methods, as qualitative data can provide greater insight into the lived experience of inmates and better chart change that is beneficial to them.